Mouse models of nesprin-related diseases. (19th June 2018) - Zhou, Can; Rao, Li; Warren, Derek T.; Shanahan, Catherine M.; Zhang, Qiuping
Abstract : Nesprins (nuclear envelope spectrin repeat proteins) are a family of multi-isomeric scaffolding proteins. Nesprins form the LInker of Nucleoskeleton-and-Cytoskeleton (LINC) complex with SUN (Sad1p/UNC84) domain-containing proteins at the nuclear envelope, in association with lamin A/C and emerin, linking the nucleoskeleton to the cytoskeleton. The LINC complex serves as both a physical linker between the nuclear lamina and the cytoskeleton and a mechanosensor. The LINC complex has a broad range of functions and is involved in maintaining nuclear architecture, nuclear positioning and migration, and also modulating gene expression. Over 80 disease-related variants have been identified in SYNE - 1/2 (nesprin-1/2) genes, which result in muscular or central nervous system disorders including autosomal dominant Emery–Dreifuss muscular dystrophy, dilated cardiomyopathy and autosomal recessive cerebellar ataxia type 1. To date, 17 different nesprin mouse lines have been established to mimic these nesprin-related human diseases, which have provided valuable insights into the roles of nesprin and its scaffold LINC complex in a tissue-specific manner. In this review, we summarise the existing nesprin mouse models, compare their phenotypes and discuss the potential mechanisms underlying nesprin-associated diseases.